2008
DOI: 10.1029/2007wr006380
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and predicting deep percolation under surface irrigation

Abstract: [1] A lysimeter experiment was conducted in southeastern Australia to quantify the deep percolation response under irrigated pasture to different soil types, water table depths, and ponding times during surface irrigation. Deep percolation was governed by the final infiltration rate of the subsoil, the ponding time, the water table depth, and the amount of water stored in the rootzone between saturation and field capacity. These key variables were used to characterize both steady-and nonsteady-state percolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 22 publications
3
52
0
Order By: Relevance
“…This simple model was readily interpretable. It supported that steady-state percolation during irrigation, as represented in the conceptual model developed by Bethune et al (2008), was the dominant process contributing to DP in the lysimeter experiment. However, non-steady-state percolation, which was also represented in the conceptual model, was likely to be a minor process contributing to DP and may even be not identifiable from the experimental data set.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This simple model was readily interpretable. It supported that steady-state percolation during irrigation, as represented in the conceptual model developed by Bethune et al (2008), was the dominant process contributing to DP in the lysimeter experiment. However, non-steady-state percolation, which was also represented in the conceptual model, was likely to be a minor process contributing to DP and may even be not identifiable from the experimental data set.…”
Section: Discussionmentioning
confidence: 53%
“…SELLE AND MUTTIL: TESTING THE STRUCTURE OF HYDROLOGICAL MODELS Bethune et al (2008) found, using the conceptual model, that steady-state percolation during irrigation was the dominant process contributing to deep percolation on most of the studied soils. Non-steady-state percolation (redistribution) was also important for some soil types.…”
Section: Conceptual Model Of Deep Percolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference crop evapotranspiration (ETo) was calculated using the method described by Hargreaves and Samani [37]. Estimation of actual evapotranspiration (AET) was calculated assuming an average crop coefficient (Kc) equal to one, as recommended for surface irrigated grazing pastures [38][39][40]. AET was calculated by converting daily ETo estimates to hourly ETo and multiplying it by time to field capacity tfc which was defined as the total number of hours from the onset of irrigation to field capacity.…”
Section: Water Balance Methodsmentioning
confidence: 99%